Oncologic and reproductive outcomes of borderline ovarian tumors in Indian population - Sarita Kumari; Sunesh Kumar; Neerja Bhatla; Sandeep Mathur; Sanjay Thulkar; Lalit Kumar (Elsevier, 2021)
Borderline ovarian tumor (BOT) is characterized by atypical epithelial proliferation without stromal invasion and majority are diagnosed at early stages and in women of reproductive age group. A retrospective review of medical records of patients diagnosed with BOT and on regular follow up at All India Institute of Medical Sciences New Delhi, during a five-year study period from March 2014 to March 2019 was performed. Surgical treatment was classified as radical, fertility sparing surgery (FSS) or cystectomy. Surgical staging was defined as complete, partial or unstaged. Median age of seventy-five women was 32 years. Follow up period ranged from 22 to 61 months (median 36 m). Radical surgery was done in 34 (45.3%), FSS in 32 (42.6%) and cystectomy in 9 (12.0%) women. Complete surgical staging was performed in 22 (29.3%), partial staging in 23 (30.6%) and 30 (40%) were unstaged. During the follow up period, 98.7% patients were alive and 90.7% were free of recurrence. Median time to recurrence was 35 months. Recurrence rate was 33.3% in cystectomy vs 6.2% in oophorectomy (p = 0.03). All seven recurrences were in unstaged (six) or partially staged patient (one). Six recurrences in ovary were salvaged by surgery and recurrent disease was of borderline histology. Spontaneous conception and live birth rate was 42.1%. FSS is a safe procedure and should be considered in a young patient with early stage disease and desirous of future fertility. Spontaneous conception and live birth rates after fertility sparing surgery in patients with BOT are modest.